Challenges and Choices: A Multidistrict Analysis of Statewide Mandated Democratic Engagement. (April 2018) - Marsh, Julie A.; Hall, Michelle
This article seeks to deepen our understanding of the nature and quality of democratic participation in educational reform by examining the first-year implementation of California's Local Control Funding Formula (LCFF) mandating civic engagement in district decision-making. Drawing on democratic theory, empirical literature, and data from 10 districts, we find that even when district leaders committed to involving stakeholders in decision-making, achieving this vision was often constrained by power imbalances, deeply engrained institutional habits, and limited capacity. We also find that climates of trust, support from external organizations, and homogeneity appeared to provide the foundation for deeper, broader democratic engagement in a few cases. The article concludes with implications for policy, practice, and future research.